A case of heteropaternal superfecundation identified by microhap sequencing of maternal plasma cell-free DNA: A case of HS identified by microhap sequencing. (March 2021) - Ou, Xueling; Bai, Zhaochen
Highlights: A paternity test case involving dizygotic twins and two alleged fathers ( AF1 and AF2 ). Microhap sequencing of cell-free DNA in maternal plasma and relMix for data analysis. The twins were revealed to had different fathers (heteropaternal superfecundation). AF1 in relation to one of the twins while excluding AF2 with regard to both twins. Standard short tandem repeat (STR) analysis employed to confirm the results. Abstract: Heteropaternal superfecundation (HS) refers to the fertilization of two or more oocytes by spermatozoa from different male partners during the polyovulatory period. The present study reported a newly discovered case of HS in the 10th week of gestation, in a case of disputed paternity involving a pair of female twins and two alleged fathers ( AF1 and AF2 ), based on a custom-designed microhap sequencing assay and R package relMix for data interpretation. The results suggested that the twins had different biological fathers, e.g., HS, and indicated the paternity of AF1 in relation to one of the twins while excluding AF2 with regard to both twins. Standard short tandem repeat (STR) analysis was employed to confirm the paternity of the heteropaternal twins. The reported case indicates that HS may occur in paternity cases with dizygotic twins, and microhap, as a novel type of highly polymorphic marker proved to be suitable for mixture deconvolution, should be able to resolve this question effectively and noninvasively at the early stage of pregnancy.